An investigation into respiratory health problems of workers at stone crushing industries in Bangladesh - Ehtesham Kabir; Aminul Islam; Md. Taufikuzzaman (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - Occupational exposure to dust is a major health and safety concern for workers in developing countries. Such laborers are often exposed to dust without being aware of its threat to their health. In the process of crushing stone, mineralogical materials are released into the environment. The material includes dust, fumes, ashes or other industrial waste which may constitute toxic elements. The purpose of this paper is to investigate the respiratory health problems of stone crushing industry workers in Bangladesh. Design/methodology/approach - This cross-sectional descriptive research study was conducted by adopting a multi-method approach. Data were collected by use of a questionnaire survey, focus group discussions, in-depth interview and spirometric examinations. Focus group discussions and questionnaire surveys were conducted among 240 workers. The respondents were divided in six groups for the spirometric examination. The questionnaire was formulated by following standards set by the American Thoracic Society Division of Lung Disease questionnaire and European Coal and Steel Community. Data on respondent's height, weight and smoking habits were collected by using a structured checklist. Meanwhile, lung functions were assessed by spirometry. A Statistical Package for Social Sciences was used to analyze the data. Findings - The results show that there was a significant relation between respiratory problems and inhalation of dust and particulate matter and cigarette smoking. It also shows that coughing was the most common problem among the respondents. The majority of respondents suffered from obstructive types of respiratory problems. Originality/value - Findings of the study reveals that chronic exposure to dust at stone crushing plants increases the risk of respiratory problems and the impaired lung function of workers. It also reveals that there is a significant relation between respiratory problems and inhalation of dusts and cigarette smoking. Raising awareness about health risks amongst workers could reduce these health hazards. The government should make a national policy for the prevention, control and elimination of silica exposure and silicosis. The results would help to raise awareness of the issue. Finally, it would raise awareness on respiratory health problems of workers at stone crushing industries in Bangladesh and help the government to make a policy for the prevention, control and elimination of silica exposure and silicosis, and thus enhancing public health policy and practices in the country.